Cold War on CNN, Part 15: China 1949-1972 (Jeremy Isaacs Productions, 1998)
The emergence of the People's Republic of China signals a new and dangerous phase in the Cold War. But a split between Moscow and Beijing opens the door for a change in U.S.-Chinese relations.